Phytochemicals and Antioxidant Activities of Red Oak, Red Coral and Butterhead - Nadechanok Jiangseubchatveera,; Charinrat Saechan,; Arpa Petchsomrit,; Tawikan Treeyaprasert,; Nattawut Leelakanok ,; Chadaporn Prompanya, (Tropical Life Sciences Research, 2023)
Lactuca sativa L. is an economically important vegetable that contains numerous phytochemicals. This study aimed to determine the phytochemicals in three lettuce cultivars (red oak, red coral, and butterhead) and assess their total phenolics, total flavonoids, and antioxidant activities. The dried leaves of each lettuce cultivar were macerated with hexane, ethyl acetate (EtOAc), and 95% ethanol (EtOH). Total phenolics, total flavonoids and antioxidant activities from the three solvent extracts were measured. The phytochemical screening showed that the leaves from the three lettuce cultivars contained flavonoids, hydrolyzable tannins, coumarins, steroids, and phenolic compounds. While the EtOAc fraction of the red coral lettuce showed the highest total phenolic content (9.747 ± 0.021 mg gallic acid equivalent/g) and the hexane fraction of the butterhead lettuce contained the highest flavonoids (7.065 ± 0.005 mg quercetin equivalent/g). In the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) assay, the EtOAc fraction of the red coral lettuce had the highest antioxidant capacity with an IC50 of 0.277 ± 0.006 mg/mL, whereas, in the ABTS (2,2’-azino-bis(3- ethylbenzothiazoline-6-sulfonic acid)) assay, the 95% EtOH of the red coral lettuce had the highest antioxidant capacity with an IC50 of 0.300 ± 0.002 mg/mL. All three lettuce cultivars contained high levels of phenolic content and flavonoids, which are the source of antioxidant activities. These lettuce cultivars, especially the red coral lettuce, are a potential source of natural antioxidants. Further research on the application of natural antioxidants is required to investigate the therapeutic or the neutraceutical implication of the lettuce cultivars.